ANALYSIS OF TRANSFLUTHRIN IN LIQUIDHOUSEHOLD PESTICIDE PRODUCTSAND ESTIMATION OF ITS EXPOSURE - Awaluddin Padjrin, M.
Transfluthrin is an active substance in a pyrethroid containing pesticide product used in mosquito repellent products and is commonly formulated into liquid preparation. However, if exposure to transflutrin exceeds the safety threshold, there would be a risk may lead to health problems. The aim of this study was to obtain a valid analytical method for determining the levels of transfluthrin in liquid household pesticide products, data on the levels of transfluthrin in these products, and estimation of their risk characteristics. Transfluthrin analysis was carried out using the gas chromatography method, starting from testing various validation parameters, determining the levels of transfluthrin in the sample, and calculating its exposure via the inhalation route to estimate its risk characteristics to health. As a safety threshold, the Margin of Exposure (MOE) value is used which is the ratio of the No Observed Adverse Effect Concentration (NOAEC) value of 0.0467 mg/L transflutrin to the level of transflutrin in air with the same unit. Minimum MOE for children less than 6 years is 100, while for children aged 6 years and over and adults is 30. The results showed that a suitable gas chromatography system was equipped with a Flame Ionization Detector (FID) detector at 300 ?C, injector temperature of 290 ?C, oven temperature gradient regulated, Rtx-5sil MS column, and helium, hydrogen, and oxygen gas make up rates of 25, 40, and 400 mL/min, respectively. The injection volume was 1 µL with an injection split ratio of 1:25 and a test time of 10 minutes. The linearity of the method is demonstrated in the range of 100 to 500 ?g/mL and the calibration curve is Y =0,0012X – 0,0025 and r2 = 0.9981. The Limit of Detection ) of this method is 30.4 ?g/mL while its Limit of Quantification is 75.0 ?g/mL, the precision of the method is expressed as a Relative Standard Deviation of 0.2839 to 2.0484%, and the accuracy expressed as a percent recovery of 90.8 to 95.4%. Transfluthrin levels were in the range of 1421.7-1466.5 µg/g with an estimated transfluthrin level in each room of A (14,400 L), B (25,200 L) and C (36,000 L) of 0.0000202, 0.0000116 and 0.0000081 mg/L, respectively, which are equivalent to MOE values of 2310, 4042 and 5775. Based on the overall results it can be concluded, the method for the analysis of transfluthrin in liquid preparations with GC-FID was successfully obtained and the transfluthrin levels were in the range of 1421.7 to 1466.5 µg/g, and the risk characteristics due to the use of liquid household pesticide products with the active pesticide transfluthrin, were still within safe limits.